Assessing Oral Health Care Utilization Patterns among Thai Seniors: a Study on Elderly Dental Services - วงศาสุลักษณ์, เยาวเรศ; ศรีทอง, ณัฐมนัสนันท์ (Journal of Health Science of Thailand, 2024)
According to the 8th National Oral Health Survey conducted in 2017 (B.E. 2560), the population aged 60 to 74 years revealed that 56.1% of this age group had at least 20 usable permanent teeth in use, 39.4% had both 20 usable permanent teeth along with 4 pairs of posterior teeth. However, 8.7% had the problem of complete tooth loss, and 42.6% required partial dentures. Additionally, 2.7% required complete dentures, while 52.6% of the elderly had untreated tooth decay. Moreover, 16.5% had root caries. The previous national survey also revealed a low proportion of people accessing oral health services. The objective of this study was to compare the utilization of oral health services among the elderly between 2019 (B.E. 2562) and 2021 (B.E. 2564). Furthermore, it aimed to analyze the correlation between the utilization of oral health services and various factors; as well as to identify issues obstacles, and recommendations for policy development in improving of the national elderly oral health service system. The results showed that the frequency of dental service visits within a 12-month period in the years 2019 and 2021 was relatively low across all elderly age groups. Among those aged 60-64 years had the highest number of dental visits, accounting for 39.7% and 38.8% for 2019 and 2021, respectively. Accessibility to dental services among the elderly remained limited and relatively low. The most commonly utilized dental services were tooth extractions, accounting for 47.23% and 41.2%, respectively. The study also identified the reasons for not availing the available welfare rights within the service. In both 2019 and 2021, the primary reason for not utilizing the welfare rights was the extended waiting period, accounting for 59.9% and 61.6% respectively. The study also found that a significant proportion of the sampled elderly group had advanced and severe oral diseases. To address the prevention of severe oral diseases, it was suggested that comprehensive public health measures should be reviewed and implemented, starting from the working-age group. The development of a networked dental service model for the elderly in various levels of public hospitals was recommended, considering the limitations of the government service system. In conclusion, the study emphasizes the need for increased awareness among dental personnel to adjust their mindset, attitudes, and knowledge about oral health care. Additionally, policy recommendations are suggested to enhance the existing benefits of dental care and to promote the importance of preventive measures over treatment.